Effect of Potassium Fertilization on Growth and Head Rice Yield of Rice (Oryza sativa L.) Merah Wangi Variety - Fanata, Wahyu Indra Duwi; Usmadi, Usmadi; Ramadhan, Galang Rizki (Jurnal ILMU DASAR, 2020)
The fertilization management is one strategy to optimize the quantity and quality of rice production. Our study was aimedto investigate the effect of potassium fertilization several agronomical parameters andthe rate of head rice after milling process. The study was conducted from March 2018 to July 2018 in the Agrotechnopark experimental field University of Jember in District of Sukorambi, Jember. Randomized Block Design (RBD) was used with the frequency of potassium chlorice (KCl) fertilization asthe single factor. The conducted potassium treatments were as follows: without KCl fertilization (control), one-time KCl fertilization, two times KCl fertilization, three times KCl fertilization and each fertilization level was conducted by sixrepetitions. The agronomic parameters such as plant height, tiller number, flowering time, rate of productive tillers, grain number per panicle, weight of 1000 grains, and percentage of filled grain were analyzed and percentage of head rice rate was determined as quality parameter. Our results showed that different treatment of potassium did not significantly affect the plant height, tillernumber, flowering time, rate of productive tillers, total grains per panicle, and weight of 1000 grains. On the other hands, the percentage of filled grainand the rate of head rice after milling were significantly increased by potassium fertilization. Compare to the control treatment, three times potassium fertilization resulted 9.24% and 13.83% increase of filled grain and head rice after two times milling, respectively. Our result suggest that potassium fertilization is important for grainquality of Merah Wangi rice variety. Keywords: Merah Wangi, potassium fertilization, growth, physical quality.